Regional repositories, reintermediation and the new GMS contract: cardiovascular disease in Tayside. - Sullivan, Frank M.; McEwan, Neil; Murphy, Gavin (Informatics in Primary Care, 2003)
The new contract for general medical practitioners will make increasing demands on the primary care informatics community. There are a number of potential ways to provide reports which meet the requirements for data on the quality of care being provided by practices. In Scotland there are four components of the national information technology strategy which make meaningful comparisons of data possible. Using cardiovascular data as an example, to describe how the community health index number, managed clinical networks (MCNs), increasing consistency of Read codes, and regional repositories of data make the acquisition, processing and use of data more straightforward. Clinicians in primary and secondary care enter data during consultations and see the results of consultations recorded elsewhere. Because all data from the region are able to be Read coded according to prespecified templates, we are able to indicate to practices where they are in relation to the new contract targets and indicate which patients need to be seen, or excluded from, calculations. Effectively integrated management is facilitated by provision of regular prompted recall and review of people with chronic disease by multidisciplinary teams collaborating across the health service and into the community. In Scotland, use of newer informatics tools are proving to be useful contributions from primary care computing to equitable, evidence-based care.